Speeches by the defeated: Abascal, Pezuela and De la Serna in front of the war in Charcas (1809-1825) - Davio, Marisa (2018)
The article addresses the perspectives of some representatives of the realist side in charge of leading the war against the revolutionaries in Charcas, based on the analysis of their speeches and the strategies they had to devise to convince the population about their political cause and the experiences they had on the battlefield. The starting point is the conflict caused by the events that took place in Chuquisaca and La Paz in 1809 and the subsequent war that began after the proclamation of the junta of Buenos Aires in 1810 until the end of the war.